Development and Evaluation of a Novel Inhalable Liposomal Powder Co-Encapsulating ASSNAC and Pirfenidone via Spray Freeze-Drying for Targeted Pulmonary Fibrosis Therapy - Qinxiu Zhang; Shouwei Sun; Miaomiao Lu; Runxin Qin; Junxuan Ren; Lianjie Yao; Dianlong Jia; Jinjie Chang; Xiaohong Chu; Rui Wang; Fang Liu; Jun Li (Pharmaceuticals, 2026)
Background: Pulmonary fibrosis (PF) is a progressive lung disease with limited therapies. Oral Pirfenidone (PFD), an approved anti-fibrotic, shows poor lung bioavailability and significant toxicity. S-Allylmercapto-N-acetylcysteine (ASSNAC) has been demonstrated to possess significant anti-inflammatory and antioxidant properties. Methods: In this study, dry powder inhaler formulations (DPIs) co-encapsulating ASSNAC and PFD in liposomes are reported. The formulation was prepared via spray freeze-drying (SFD) using L-leucine as both a cryoprotectant and a surface morphology modifier. The interfacial enrichment of L-leucine during atomization and freezing created a hydrophobic, corrugated surface that lowered particle surface energy, prevented liquid/solid bridge formation, and reduced hygroscopicity. Results: The resulting liposomal powders exhibited optimal aerosol performance: fine particle fraction (FPF) of 61.08% ± 2.45% and mass median aerodynamic diameter (MMAD) of 2.22 ± 0.11 µm. Cellular studies demonstrated that dual-loaded liposomes were efficiently taken up by Beas-2B and HFL-1 cells, with no cytotoxicity (cell viability > 90%) and negligible hemolysis. In the TGF-β1-induced in vitro fibrosis model, the combined treatment exerted prominent therapeutic effects. This regimen preserved normal epithelial morphology, accelerated wound repair, suppressed fibroblast invasiveness, and lowered the expression levels of Collagen I, Collagen III, and α-SMA. In bleomycin-induced pulmonary fibrosis rats, inhaled ASSNAC + PFD liposomal powder markedly relieved lung tissue injury and collagen accumulation. It restored redox balance and lowered pulmonary TGF-β1, hydroxyproline and collagen III levels. The formulation blocked TGF-β1 signaling and fibrotic gene expression. Conclusions: Pulmonary administration avoids oral pirfenidone-induced liver and stomach toxicity. Collectively, the ASSNAC + PFD co-encapsulated liposomal dry powder produced by SFD represents a safe and efficacious therapeutic strategy for PF.